Silting patterns in the reservoirs of small‐ and medium‐sized earthen check dams in humid subtropical monsoon regions. Issue 13 (14th August 2019) - Kang, Ranbir S.; Chacko, Elizabeth; Kaur, Dhian; Viadero, Roger
ABSTRACT: Silting of reservoirs is a ubiquitous process whenever water is impounded. Despite substantial work on the rates of silting, the spatial pattern of silting in reservoirs is not clearly understood. While it is anticipated that the variability of silting increases with decreasing reservoir size, not much is known about siltation in subtropical humid regions affected by monsoon rainfall. This paper presents the initial results of geomorphic analysis of six earthen check dams in the Shiwalik foothills of the Himalayas (India) in areas that are inhabited by high proportions of disempowered populations. These check dams include three small‐sized dams (Dhamala‐II, Rel Majra and Sukhomajri‐II) and three medium‐sized dams (Bunga‐I, Parachh‐II and Siswan). Field data were collected from each reservoir. The methods used included spatial interpolations of bed depth and silt thickness in each reservoir, Structure from Motion photogrammetry to extract multiple channel cross‐sections from photographic scans along tributary mouths, texture analysis of bed and bank materials, and visual observations of hill slopes around the check dams. Based on this study, silt tended to concentrate either in the middle portion of the reservoir or near the dam; however, silt accumulation did not always occur along the dam or in the deepest portion of the reservoirs. Areas located downstream from these check dams are heavily used for various human activities and the channel network has almost been eliminated. While these earthen check dams may be cost‐effective tools for water conservation in economically marginalized areas, if abandoned, these structures may pose a physical hazard to downstream communities. © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd. Abstract : Analysis of earthen check dams in the Shiwalik foot hills of the Himalayas (India) dominated by monsoon rainfall reveals that: Silt tends to concentrate either in the middle portion of the reservoir or near the dam. Silt accumulation does not always occur along the dam or in the deepest portion of the reservoir. Areas located downstream from these check dams are heavily used for various human activities and the channel network has almost been eliminated.